Upfront use of plerixafor and granulocyte-colony stimulating factor (GCSF) for stem cell mobilization in patients with multiple myeloma: efficacy and analysis of risk factors associated with poor stem cell collection efficiency*. Issue 5 (4th May 2017) - Ogunniyi, Adebayo; Rodriguez, Mabel; Devlin, Sean; Adel, Nelly; Landau, Heather; Chung, David J.; Lendvai, Nikoletta; Lesokhin, Alexander; Koehne, Guenther; Mailankody, Sham; Korde, Neha; Reich, Lilian; et al.
Abstract: Plerixafor (P), an agent that selectively and reversibly binds to the chemokine receptor CXCR4, has been approved in combination with G-CSF (P + G-CSF) for stem cell (SC) mobilization in patients with multiple myeloma (MM). The goal of this study was to determine the SC collection success rate of P + G-CSF using a clinically relevant outcome defined as the ability to collect at least 5 × 10 6 CD34 + cells/kg to allow safely two transplants, and identify risk factors impacting SC mobilization. One hundred and thirty-eight patients were mobilized with P + G-CSF upfront following induction. The SC collection success rate was 92.8%. We identified exposure to lenalidomide alone ( p  = .038), WBC count <4 × 10 3 /mcL prior to mobilization ( p  = .01) and non-African American race ( p  = .019), as risk factors for low efficiency by multivariate analysis. This study demonstrates that P + G-CSF is highly efficient in MM patients and provides strong support for its upfront use in SC collection for MM patients.